Molecular cytogenetic identification of new wheat-rye 6R, 6RS, and 6RL addition lines with resistance to stripe rust and powdery mildew - Ren, Tianheng; Sun, Zixin; Hu, Yuling; Ren, Zhenglong; Tan, Feiquan; Luo, Peigao; Li, Zhi (Frontiers in Plant Science, 2022)
Stripe rust and powdery mildew are devastating diseases that have severe effects on wheat production. Introducing resistant genes/loci from wheat-related species into the wheat genome is an important method to improve wheat resistance. Rye (Secale cereale L.) is a cross-pollinating plant and is the most important related species for wheat genetic improvement. In this study, we developed three 6RS ditelosomic addition lines, three 6RL ditelosomic addition lines, and two 6R disomic addition lines by crossing common wheat cultivar Chuannong 25 and rye inbred line QL2. The chromosome composition of all new lines was confirmed by nondenaturing fluorescence in situ hybridization (ND-FISH) and molecular marker analyses. Disease responses to different Puccinia striiformis f. sp. tritici (Pst) races and Blumeria graminis f. sp. tritici (Bgt) isolates and cytogenetic analysis showed that the resistance of the new lines was derived from the rye chromosome 6R of QL2, and both arms (6RS and 6RL) may harbor resistance genes against Pst and Bgt. These new lines could be used as a promising bridging parent and valuable genetic resource for wheat disease resistance improvement.